An Institutional Framework for Comparing Emerging Market Currency Boards - Dal Corso, Marie (Washington, D.C. : International Monetary Fund, 2004)
This paper offers an in-depth review of the institutional arrangements underlying existing currency boards (CBAs) in Argentina (until 2001), Eastern Europe, and Asia. An index of precommitment is derived from an analysis of legislative frameworks and monetary policy operations. The index covers features associated with monetary and exchange rate credibility such as: (i) clarity of legal basis, (ii) quality of reserve coverage, (iii) coverage of monetary aggregates, (iv) claims on reserves, (v) operational autonomy, (vi) transparency and accountability, and (vii) escape clauses. The paper concludes with a discussion of flexibility and credibility trade-offs and exit issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet